PENYELENGGARAAN PEMERINTAHAN KHUSUSNYA BAGIAN HUKUM DI SEKRETARIAT DAERAH KABUPATEN MADIUN - Yuda Nata, Setyo Nugroho; Boerhan, Soebagio (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The research with the title "Government Administration, especially the Legal Section at the Regional Secretariat of Madiun Regency", is motivated by the administration of the Madiun district government, especially the legal department. Based on this, the authors drew two problem formulations in this study, including: (1). What is the function of the Legal Section of the Madiun Regency Regional Secretariat in administering government within the Madiun Regency Government? (2). What are the factors that hinder the Legal Section of the Madiun Regency Regional Secretariat in carrying out its duties and functions in the administration of regional government within the Madiun district government? The legal theories used in this study include the theory of decentralization and the theory of establishing good laws and regulations. The research method uses normative juridical research, namely research used to examine legal principles and principles. The research was conducted at the Regional Secretariat of the Madiun Regency Legal Department of the Madiun Regency Regional Secretariat (SETDA), regarding the role of the legal department in administering government. The results of the research that the authors obtained included: (1) the function of the legal section of the regional secretariat of Madiun Regency through the administration of regional government with an average performance of very well (2). Factors that hinder the legal division of the Madiun Regency Secretariat in administering government include: (a). the lack of human resources in the legal section of the madiun regional secretariat has resulted in a high workload which is feared to have an impact on future performance decline. (b). there isno structured, continuous and massive training for statutory subdivision staff. (c). the lack of interest in the functional position of the drafter of legislation due to the difficulty in obtaining credit point numbers for promotion.